Measuring the Subjective Well-being of Teachers - Rosa Isela Gluyas Fitch; Yutzil Tania Cadena Pedraza; María del Carmen Romero Sánchez Sánchez; Monica Georgina Cinco Basurto (Universitas Ahmad Dahlan, 2017)
Abstract This paper presents an instrument, designed using scientific methods, to measure the subjective well-being of teachers in relation to their work and to variables from life experience. Participant teachers work at the basic educational level in private institutions created by the civil society that attend to the needs of the socio-economically vulnerable populations outside the state’s system. The Cronbach Alfa index and exploratory factor analysis were used to establish the reliability and validity of the instrument applied to 183 Mexican teachers in the pilot test. Conclusions pint out to possible uses of this validated instrument for the design of strategies that favor the integral well-being of the future generations of teachers and a substantial improvement in the quality of education. Keywords: subjective well-being, instrument, teacher, health, and satisfaction.